The Analysis of Rhetorical Devices in Two Tesla Promotional Videos - Jihan Nurul Savira Alyanto; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study was conducted to discover the rhetorical devices Elon Musk used when delivering Tesla promotional videos, namely the Tesla Unveils Model 3 and Tesla Semi & Roadster Unveil. This study also wants to examine the messages that are underscored by the use of rhetorical devices. In this study, the writer used Harris’ (2018) theory of rhetorical devices as the leading theory. The study was done by applying qualitative content analysis (QCA). The study showed that Elon Musk utilized climax, asyndeton, polysyndeton, sentential adverb, exemplum, amplification, anaphora, and hypophora in Tesla Unveils Model 3. Rhetorical devices such as climax, asyndeton, sentential adverb, exemplum, amplification, anaphora, and hypophora are found in Tesla Semi & Roadster Unveil. However, the data regarding polysyndeton is non-existent in Tesla Semi & Roadster Unveil. Each rhetorical device employed by Elon Musk helped underscore the messages in both videos. Ultimately, rhetorical devices affect the promotional video positively as they help amplify the meaning of the speech.